Epitaxial Dirac Semimetal Vertical Heterostructures for Advanced Device Architectures. (12th February 2022) - Rice, Anthony D.; Lee, Choong Hee; Fluegel, Brian; Norman, Andrew G.; Nelson, Jocienne N.; Jiang, Chun Sheng; Steger, Mark; McGott, Deborah L.; Walker, Patrick; Alberi, Kirstin
Abstract: Exploiting the extraordinary transport and optical properties of 3D topological semimetals for device applications requires epitaxial integration with semiconductors to carefully control carrier transport, yet no studies have established heteroepitaxy on top of any topological semimetals to date. Here, a novel approach toward fabricating heterostructures is demonstrated by epitaxially incorporating the Dirac semimetal Cd3 As2 between Znx Cd1‐x Te and CdTe layers via molecular beam epitaxy on GaAs (001) substrates. The approach utilizes the higher energy (001) surface of Cd3 As2 to stabilize 2D epitaxy of zinc blende semiconductors. To demonstrate the impact heterostructure formation offers to device performance, an all‐epitaxial, barrier‐type vertical photodetector is fabricated that accesses a different carrier separation mechanism than previously reported non‐epitaxial junctions and consequently exhibits significantly reduced dark currents. The results highlight the important role that epitaxial integration can play in accessing advanced architectures for topological semimetal‐based devices. Abstract : Heteroepitaxy of semiconductors is demonstrated on top of the topological Dirac semimetal Cd3 As2 . The ability to incorporate topological semimetals within complex semiconductor device structures offers new pathways for advanced architectures with superior control of majority and minority carrier transport, as demonstrated for a barrier‐type photodetector.